A Competence Comparison of Learning Results Using Problem Based Learning With Discovery Learning on Integrated Themat Learning in Class IV Basic School - Elmita Waslina; Farida F; Yanti Fitria; Mudjiran Mudjiran (Postgraduate School, Universitas Negeri Padang, 2019)
This study aims to compare the application of Problem Based Learning learning models to Discovery Learning students in grade IV SD 187 Pekanbaru. This research was conducted with experimental research methods with a comparative approach.